2023
DOI: 10.1111/flan.12733
|View full text |Cite
|
Sign up to set email alerts
|

Investigating L2 writers' uses of machine translation and other online tools

Kimberly Vinall,
Wen Wen,
Emily A. Hellmich

Abstract: New technologies have had a substantial impact on L2 learners' writing processes. Given the continuous nature of technological evolution, more work is needed to document L2 writers' learner‐initiated technology use, particularly their use of machine translation (MT) tools. This need is further solidified by recent calls for new pedagogical approaches to better prepare learners to use MT critically. The current study uses screen recordings, retrospective recall, and interviews to document what online tools L2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In addition, through the advancement in NMT, detection has become increasingly challenging for instructors in the field of language teaching, when the writer's actual writing ability without the use of MT tools is unknown (Stapleton & Ka Kin, 2019). There are concerns that MT can be detrimental where MT prevents learners from engaging in the writing process (Vinall & Hellmich, 2021). However, the readily accessible tool is omnipresent and an unavoidable part of our daily lives (Groves & Mundt, 2015).…”
Section: Role Of Mt For Language Instruction and Writing Classesmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, through the advancement in NMT, detection has become increasingly challenging for instructors in the field of language teaching, when the writer's actual writing ability without the use of MT tools is unknown (Stapleton & Ka Kin, 2019). There are concerns that MT can be detrimental where MT prevents learners from engaging in the writing process (Vinall & Hellmich, 2021). However, the readily accessible tool is omnipresent and an unavoidable part of our daily lives (Groves & Mundt, 2015).…”
Section: Role Of Mt For Language Instruction and Writing Classesmentioning
confidence: 99%
“…In some studies, it was found that students were discouraged from even single-word translations (Vinall & Hellmich, 2021). In other studies, MT was considered to be a form of plagiarism (Stapleton & Ka Kin, 2019).…”
Section: Teachers' Beliefs and Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This knowledge encompasses the knowledge of the affordances of a given tool in relation to a task, an ability to exploit these affordances appropriately and in a timely manner, in isolation or in conjunction with other tools, and an ethical reflection on what the use-or nonuse-of a tool produces in the development of knowledge and in relationships with others. If we take the example of the use of MT for a writing task (Vinall et al, 2023), metatechnolinguistic competence would comprise the factual knowledge that a translation will, for example, be better if the query in the machine translator is made at sentence level, rather than at the level of a group of words isolated from its context. Yet, it should also comprise the reflection that the systematic use of MT to translate a text from L1 to Lx might help learners perform a writing task but also create among them "an illusion of linguistic ability," as Kern (2024, this issue, p. 522) puts it.…”
mentioning
confidence: 99%